Handbook Global History of Work - Hofmeester, Karin; van der Linden, Marcel (De Gruyter Reference, 2017)
What is the day-to-day reality for workers in various parts of the world, and how was it in the past? How do they work today, and how did they work in the past? Did workers ever protest? If so, how? These and many other questions comprise the field of the global history of work - a young discipline that is introduced with this handbook.